T105. GENETIC INFLUENCES OF NEURODEVELOPMENTAL GENES ON SEVERE MENTAL ILLNESSES - Ashitha, SNM; Ganesh, Suhas; Purushottam, Meera; Viswanath, Biju; Jain, Sanjeev (European neuropsychopharmacology, 2023)
Bipolar disorders (BP) and schizophrenia (SCZ) show impairment in social interaction and communication deficits often seen in children with Autism Spectrum Disorders (ASD). Genetic evidence suggests that a substantial fraction of genetic influences transcend clinical diagnostic boundaries of psychiatric disorders. We have sequenced more than 300 individuals from families with severe mental illnesses (SMI), including 80 BP and 63 SCZ individuals, 60 family and population controls each. We investigated the mutational burden on neurodevelopmental genes implicated in ASD in BP and SCZ Whole Exome Sequencing (WES) datasets to identify shared pathobiological roles in BP and SCZ. WES was performed using the Illumina platform. Deleterious variants were identified following a stringent pipeline. The Simons Foundation Autism Research Initiative gene database- that scored genes based on the strength of the evidence available- was used to screen for variations in ASD genes in BP and SCZ datasets. We then compared our findings with publicly available global genetic repositories: SCHEMA and BipEx for SCZ and BP respectively. We identified a total of 188 SFARI ASD genes (17%) carrying pathogenic variants in our cohort:122 and 66 genes in cases and controls, respectively. Cases included 111 high-confidence, strong candidate ASD genes that were enriched for nervous system development (p- 1e-05), axon guidance (2.6e-7), opening of presynaptic calcium channels (3.5e-05) and oligodendrocyte precursor cell markers (2.23e-05). 28 genes were common to both SCZ and BP subjects which were significantly enriched for genes CACNA1G, CACNA2D1, CHRNA7, CACNA1E, and CACNA1B involved in presynaptic voltage-gated calcium channel activity (5.26e-07). A similar analysis with SCHEMA and BipEx showed increased mutational frequency in genes CACNA1G, CACNA2D1, NRXN1 and MYO5A mirroring our findings. SCHEMA showed a significantly higher enrichment for SFARI genes than BipEx dataset (1e-05) indicating a stronger genetic correlation between SCZ and ASD than BP and ASD. Our analysis hints at dysregulated neurodevelopment as an integral pathology of SCZ and BP. We will further look into the expression patterns of these genes for their precise spatiotemporal influences and perform protein-interaction network analysis to identify probable molecular mechanisms of action. This would enable us to delineate prenatal/postnatal risk periods during the process of neurodevelopment, identify brain regions and cell-types specifically affected by neurodevelopmental gene perturbations.